Analysis of Village Fund Management in Improving Community Welfare in Panyangkalang Village, District Laikang Takalar Regency - Nasrun, Siti Rahayu; Asdar,; Warda, (AKSIOMA : Jurnal Manajemen, 2025)
This study aims to analyze the management of Village Funds in improving community welfare in Panyangkalang Village, Laikang District, Takalar Regency. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The management of Village Funds was examined based on the stages outlined in Regulation of the Minister of Finance No. 145 of 2023, which include planning, implementation, administration, and reporting. Community welfare was measured using indicators from Herbert A. Simon, namely knowledge, participation, program benefits, and transparency and accountability. The findings show that the planning and implementation processes involved community participation, although not yet evenly distributed. Village Fund programs have provided tangible benefits to some residents, but transparency of information and equitable distribution of benefits still need improvement. Strengthening the capacity of village officials and expanding community involvement are key to enhancing the effectiveness of Village Fund management.
Keywords: Village Fund; Welfare; Participation; Transparency; PMK 145/2023